Clustering of feeding strategies to improve the evaluation of enteric and slurry methane emissions in dairy cows: an observational study based on Italian dairy farms - Giulia Ferronato; Noemi Tobanelli; Anna Simonetto; Gianni Gilioli; Andrea Formigoni (Italian Journal of Animal Science)
The dairy sector is facing increasing challenges in terms of its environmental impact. Methane (CH4) is a focal point of research due to its role in enteric emissions from livestock. This study investigates the effects of various feeding strategies on CH4 emissions from lactating Holstein cows fed total mixed ration (TMR) silage-based diets. Four different equations for estimating CH4 emissions were chosen according with accuracy and equation variables, and then compared checking whether diet composition has an effect on average emission levels. Only Mills equation detected differences between nutritional clusters. Considering this equation on average, the CH4 emissions were equal to 460.36 ± 46.95 g/d, 18.90 ± 1.57 g/kg DMI, 12.89 ± 2.83 g/kg FPCM, equal to a loss of 5.93% of gross energy intake. Clustering based on feed composition identified four distinct groups of diets, with no statistically significant difference in CH4 emissions. The highest emissions were found in the nutritional cluster with higher fibre and starch content, with methane production (MeP) reaching 485.85 g/d, 19.47 kg/kg DMI and 14.82 kg/kg FPCM. This indicates that diet nutrients profile significantly impacts CH4 emissions, underscoring the importance of adopting sustainable feeding strategies in dairy production. Notably, a positive correlation exists between MeP and milk productivity, while methane intensity negatively correlates with feed efficiency. The findings emphasise the necessity for context-specific emission factors and underscore the importance of implementing sustainable feeding practices to mitigate CH4 emissions enhancing the efficiency of dairy production systems.